1996
DOI: 10.1016/0165-0327(96)00042-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and autonomic regulation in major depressive disorder: an exploratory study

Abstract: Spectral analysis of fluctuations in heart rate and blood pressure was employed to explore sympathetic and parasympathetic cardiovascular control mechanisms in relation to trait anxiety in major depressive disorder. Sixteen drug-free female depressed patients were divided into two groups: those who were high on trait anxiety (HTA, n = 9) and those who were normal or low on trait anxiety (LTA, n = 7). In patients and age-matched female controls (n = lo), heart rate (HR), blood pressure (BP; Finapres device) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Previous studies comparing the resting HRV in healthy depressed participants with participants that were not depressed have reported inconsistent results. Some studies have reported no differences (Dishman et al, 2000;Hughes and Stoney, 2000;Shinba et al, 2008;Tulen et al, 1996). However, the most consistent finding is that anxiety and depressed mood are related to low levels of HF during exposure to stress (Hughes and Stoney, 2000;Ledowski et al, 2005;Light et al, 1998;Shinba et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies comparing the resting HRV in healthy depressed participants with participants that were not depressed have reported inconsistent results. Some studies have reported no differences (Dishman et al, 2000;Hughes and Stoney, 2000;Shinba et al, 2008;Tulen et al, 1996). However, the most consistent finding is that anxiety and depressed mood are related to low levels of HF during exposure to stress (Hughes and Stoney, 2000;Ledowski et al, 2005;Light et al, 1998;Shinba et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Although reduced HRV based on 24-hour recording of the heart rate is associated with depression in patients with coronary artery disease (17,18), short-term HRV measured at supine rest does not differentiate depressive patients from their healthy controls (9,19,20). No data exist of the relationship between HRV and depression in the general population.…”
Section: Introductionmentioning
confidence: 90%
“…However, the effects of psychological symptoms, such as hostility, on HRV may only be revealed in recordings that are sufficiently long to produce transactions between individuals and their environments (15). Posture may also modify results during short-term recordings, as persons with panic disorder or anxiety have been found to have altered HRV only in the standing position and not at supine rest (8,9,11,19).…”
Section: Psychological Factors and Autonomic Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…stronger vagal withdrawal, compared to patients low on trait anxiety (Tulen et al, 1996). In a study involving different subgroups of unmedicated MDD patients -MDD without comorbidity, MDD with comorbid panic disorder and/or posttraumatic stress disorder and MDD comorbid with generalized anxiety disorder -decrease in HRV measures was most pronounced in patients with comorbid generalized anxiety disorder .…”
Section: Hrv In Major Depressive Disorder (Mdd)mentioning
confidence: 99%